Antifungal activity of probiotic strain Lactiplantibacillus plantarum MYSN7 against Trichophyton tonsurans - Vanitha, P. R.; Somashekaraiah, Rakesh; Divyashree, S.; Pan, Indranil; Sreenivasa, M. Y. (Frontiers in Microbiology, 2023)
The primary objective of this study was to assess the probiotic attributes and antifungal activity of Lactic acid bacteria (LAB) against the fungus, Trichophyton tonsurans. Among the 20 isolates screened for their antifungal attributes, the isolate MYSN7 showed strong antifungal activity and the same was selected for further analysis. The isolate MYSN7 exhibited potential probiotic characteristics having 75% and 70% survival percentage in pH3 and pH2 respectively, 68.73% tolerance to bile, moderate cell surface hydrophobicity of 48.87% and auto aggregation percentage of 80.62%. The CFS (cell free supernatant) of MYSN7 also showed effective antibacterial activity against common pathogens. Further, the isolate MYSN7 was identified as Lactiplantibacillus plantarum by 16srRNA sequencing. Both Lactiplantibacillus plantarum MYSN7 and its CFS exhibited significant anti-Trichophyton activity in which the biomass of the fungal pathogen was negligible after 14 days of incubation with the active cells of probiotic culture (106 CFU/ml) and at 6% concentration of the CFS. Also, the CFS has inhibited the germination of conidia even after 72 hrs of incubation.Minimum inhibitory concentration of the lyophilised crude extract of the CFS was observed to be 8 mg/ml. Preliminary characterisation of the CFS showed that the active component would be organic acids in nature responsible for antifungal activity. Organic acid profiling of the CFS by using LC-MS revealed that it’s a mixture of 11 different acid and among these, succinic acid (9793.60 µg/ml) and lactic acid (2077.86 µg/ml) were predominating. Additionally, scanning electron microscopic study revealed that CFS has disrupted fungal hyphal structure significantly which showed scanty branching and bulged terminus. The study indicates the potential of L. plantarum MYSN7 and its CFS to control growth of T tonsurans. Further in-vivo studies need to be conducted to explore its possible applications on skin infections.